2022
DOI: 10.2991/aebmr.k.220307.459
|View full text |Cite
|
Sign up to set email alerts
|

Influential Factors of Sales Revenue in the Fast-Food Industry

Abstract: Fast food refers to popular catering that commercial enterprises quickly supply. The fast-food industry, which can be processed quickly and eaten anytime and anywhere, has become increasingly important in the wake of COVID-19. The purpose of this article is to study the different factors that affect the sales revenue of the fast-food industry. This study took two approaches to examine the elements that influence sales income. It is from the perspective of affecting commodity prices, and on the other hand, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…In modern society, fast food plays an important role in people's composite lifestyles (Saraniya & Kennedy, 2015). Thus, the fast-food industry (FFI) as a profitable industry began in the 1920s in the United States (Liu et al, 2022). This fast-food industry developed rapidly in modern society and became epidemic worldwide in the 1950s (Jauhari, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In modern society, fast food plays an important role in people's composite lifestyles (Saraniya & Kennedy, 2015). Thus, the fast-food industry (FFI) as a profitable industry began in the 1920s in the United States (Liu et al, 2022). This fast-food industry developed rapidly in modern society and became epidemic worldwide in the 1950s (Jauhari, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It is argued that market supply and demand of food products affect price pattern and the sales volume in relation to the delivery systems, e-commerce and advertisement (Liu et al, 2022). Wei et al (2020) found out that the ratio of online and offline profit to the total dual-channel profit of food products depends on the location of customers and the values of the logistics costs.…”
Section: Statement Of the Problemmentioning
confidence: 99%